2002
DOI: 10.1063/1.1430542
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of stressed and broken down SiO2 films at a nanometer scale using a conductive atomic force microscope

Abstract: A conductive atomic force microscope (C-AFM) has been used to investigate the degradation and breakdown of ultrathin (<6 nm) films of SiO2 at a nanometric scale. Working on bare gate oxides, the conductive tip of the C-AFM allows the electrical characterization of nanometric areas. Due to the extremely small size of the analyzed areas, several features, which are not registered during macroscopic tests, are observed. In particular, before the oxide breakdown, switchings between different conduction stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 30 publications
4
55
0
Order By: Relevance
“…Moreover, currents from 1 pA up to 1 mA can be measured. Carrier injection has been done from the substrate [6] (deep depletion has been avoided), which corresponds to the SILC generation worst case. (voltages higher than 9 V), the current progressively increases reaching the so called regime C. A second I-V curve measured at the same location ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, currents from 1 pA up to 1 mA can be measured. Carrier injection has been done from the substrate [6] (deep depletion has been avoided), which corresponds to the SILC generation worst case. (voltages higher than 9 V), the current progressively increases reaching the so called regime C. A second I-V curve measured at the same location ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Both pre-and post-RVS results, as well as the curve fitting using the FowlerNordheim (FN) tunneling theory [6], are also given in the figure. The current fluctuation observed can be attributed to charge trapping and de-trapping in the oxide [7]. Clearly, the post-RVS curve shifted upward (current is increased at a given voltage).…”
Section: Methodsmentioning
confidence: 81%
“…3. Porti et al [7] have reported that such a number could be related to the existence of the total defects (defects at the interface and in the bulk) in the oxide film and the trapping/de-trapping of charge at these defects. As shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The most accomplished works can be attributed to Porti et al (2002Porti et al ( , 2003Porti et al ( , 2007 and Wu et al (2007Wu et al ( , 2008Wu and Lin 2006). Both authors have shown that oxide degradation exhibits two aspects.…”
Section: Introductionmentioning
confidence: 96%
“…C-AFM can simultaneously map topography and current distributions of a sample. Numerous studies have been realised on thin SiO 2 films on Si substrates using this technique (Porti et al 2002(Porti et al , 2003(Porti et al , 2007Wu and Lin 2006;Wu et al 2007Wu et al , 2008Hourani et al 2011). But, at this day, no clear explanation was provided to understand the mechanisms involved at nanoscale in stressed and broken-down thin films.…”
Section: Introductionmentioning
confidence: 99%